Breast cancer and serum ferritin - Menopausal status perspective: Menopause - A fickle determinant - Narkhede, Harshal P.; Muddeshwar, Manohar G.; Mahajan, Vishakha V. (International Journal of Research in Medical Sciences, 2017)
Background: Association of raised serum ferritin levels with breast carcinoma is a well established fact on account of iron enhanced free radical mediated oestrogen induced carcinogenesis. Previous literatures report variations in serum ferritin levels with menopause, especially indicating its association with metabolic syndrome in post-menopausal women. Seldom has any study focussed upon influence of age and menopausal status towards serum ferritin level determination in breast cancer patients. Assess an impact of age and menopausal status over serum ferritin levels in patients with breast cancer and in healthy females; and their comparisons. Methods: Enzyme linked immuno-sorbent assay based estimation of serum ferritin was carried out in patients with breast carcinoma and healthy females. Objective: Age-wise and menopausal status-wise grouped numerical data were analyzed through intra- and inter-group comparisons. Results: Higher serum ferritin levels were observed in all age groups as well as pre-menopausal and post-menopausal groups of breast cancer subjects than their respective groups among healthy subjects. No particular age or menopausal status-wise pattern could be identified among cases as well as healthy controls. Conclusions: Serum ferritin levels abide no obvious influence of age or menopausal status in breast cancer patients as well as post-menopausal women devoid of metabolic syndrome. The present study reiterates the possible role of iron in breast carcinogenesis.